Study on Using the Climate Auction Model to Catalyse Energy, and Resource Efficient Buildings - World Bank (World Bank, Washington, DC, 2019)
The Pilot Auction Facility (PAF) is an auction-based pay-for-performance mechanism that was originally developed by the World Bank to attract investment to projects that reduce methane emissions. The purpose of this study was to assess whether the PAF climate auction model could be translated effectively to the residential new building sector. A qualitative review of six countries was carried out to inform the basic conditions that would need to be met for the climate auction mechanism to be successfully rolled out to the residential building sector. India was then selected as a case study to carry out a quantitative assessment of the potential impact of the mechanism.